PERSONALITY TRAITS MAHASISWA DAN DAMPAK BISNIS DIGITAL: PENGARUH TERHADAP GREEN ENTREPRENEURIAL INTENTION - Safitri, Camelia (Humano: Jurnal Penelitian, 2024)
This research explores the influence of students' personal characteristics on their participation in digital business and its impact on the digital economy. Using a quantitative approach, an online survey was conducted on 200 students. Personality traits are analyzed using the Big Five theory which includes extroversion, agreeableness, conscientiousness, neuroticism, and openness. Data were analyzed using linear regression. The research results show that personality traits have an influence on Green Entrepreneurship Intention, while economics and digital business have no influence on Green Entrepreneurship Intention, extroversion, agreeableness, and conscientiousness have a positive influence on student participation and contribution in digital business, while neuroticism and openness have an influence. negative. This research confirms the importance of personal traits in influencing students' participation in digital business and recommends strategies to increase their awareness and participation. It is hoped that the research results can support the development of more effective education and training strategies in the field of digital entrepreneurship and can increase Green Entrepreneurial Intention among students.